A Promising Approach to Preventing Gender-Based Violence and HIV Among Slum-Dwelling Youth in Nairobi, Kenya - Edwards, Katie M. (Violence against women, 2022)
Gender-based violence (GBV) and HIV are interrelated public health problems affecting numerous global communities. To date, few prevention initiatives have demonstrated reductions in GBV and HIV, and thus there is an urgency to identify effective strategies to prevent these interconnected public health crises. The purpose of the current article is to describe a gender-enhanced life skills training curriculum (GE-LSTC) currently being developed in Nairobi, Kenya. We discuss previous research relevant to the GE-LSTC; the theoretical underpinnings of the GE-LSTC; the history and context of the GE-LSTC; preliminary implementation, feasibility, and acceptability data on the GE-LSTC; and plans for further refinement and rigorous evaluation of the GE-LSTC.